The digital activism of marginalized South African gen z in higher education - Abyshey Nhedzi; Caroline Muyaluka Azionya (Humanities & Social Sciences Communications)
Abstract Despite the digital divide in South Africa and limited internet access for most students, X, formerly Twitter, played a central role in the participation of historically Black marginalized university students’ online campaign. Social media platforms have transformed how university activists connect, share ideas, and mobilize. These platforms enable students to rapidly plan, organize, and remotely execute protests, demonstrations, or movements. This article uses South African student-led campaigns protesting universities’ rapid shift to remote learning during the COVID-19 lockdown to explore student activism and counter-activism on X. Using an inductive qualitative content analysis of tweets, this research demonstrates that students view education as a human right and a pathway out of poverty, historical disadvantages, isolation, and deprivation. In contrast, this activism was met with silence and hostility from their universities’ leadership and anti-activism. Further, results show that protesting Generation Z students, particularly from historically Black marginalized universities, tagged prominent politicians and social media influencers to voice their call for assistance and inclusive solutions and amplify their need for education. Our findings provide important insights to help policymakers understand that the scars of apartheid can be addressed if inclusive solutions are implemented to online education and subsequently increase resources for historically black universities.